Performance of Bamboo Fiber Reinforced Composites: Mechanical Properties - Norliana, Bakar; Siew, Choo Chin (Trans Tech Publications, Switzerland, 2021)
Fiber Reinforced Polymer (FRP) made from synthetic fiber had been widely used for strengthening of reinforced concrete (RC) structures in the past decades. Due to its high cost, detrimental to the environment and human health, natural fiber composites becoming the current alternatives towards a green and environmental friendly material. This paper presents an investigation on the mechanical properties of bamboo fiber reinforced composite (BFRC) with different types of resins. The BFRC specimens were prepared by hand lay-up method using epoxy and vinyl-ester resins. Bamboo fiber volume fractions, 30%, 35%, 40%, 45% and 50% was experimentally investigated by conducting tensile and flexural test, respectively. Results showed that the tensile and flexural strength of bamboo fiber reinforced epoxy composite (BFREC) was 63.2% greater than the bamboo fiber reinforced vinyl-ester composite (BFRVC). It was found that 45% of bamboo fiber volume fraction on BFREC exhibited the highest tensile strength compared to other BFRECs. Meanwhile, 40% bamboo fiber volume fraction of BFRVC showed the highest tensile strength between bamboo fiber volume fractions for BFRC using vinyl-ester resin. Studies showed that epoxy-based BFRC exhibited excellent results compared to the vinyl-ester-based composite. Further studies are required on using BFRC epoxy-based composite in various structural applications and strengthening purposes.